2016
DOI: 10.5935/abc.20160060
|View full text |Cite
|
Sign up to set email alerts
|

Early Markers of Atherosclerotic Disease in Individuals with Excess Weight and Dyslipidemia

Abstract: BackgroundExcessive weight is a cardiovascular risk factor since it generates a chronic inflammatory process that aggravates the endothelial function.ObjectiveTo evaluate the endothelial function in individuals with excess weight and mild dyslipidemia using brachial artery flow-mediated dilation (BAFMD), and the association of endothelial function with anthropometric and biochemical variables.MethodsCross-sectional study that included 74 individuals and evaluated anthropometric variables (body mass index [BMI]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…FIB levels can be higher in patients with stroke versus non-stroke patients [2]. Due to the connection between elevated FIB levels and the early appearance of atherosclerosis symptoms, the increase in FIB concentration is observed in obese people, smokers, and alcohol abusers, while lower in physically active people [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…FIB levels can be higher in patients with stroke versus non-stroke patients [2]. Due to the connection between elevated FIB levels and the early appearance of atherosclerosis symptoms, the increase in FIB concentration is observed in obese people, smokers, and alcohol abusers, while lower in physically active people [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…I have read with great interest the article entitled "Early Markers of Atherosclerotic Disease in Individuals with Excess Weight and Dyslipidemia" by Menti et al 1 recently published in Arquivos Brasileiros de Cardiologia 2016; 106: 457-63. The investigators reported that fibrinogen is associated with subclinical atherosclerosis in individuals with excess weight.…”
mentioning
confidence: 99%
“…The investigators reported that fibrinogen is associated with subclinical atherosclerosis in individuals with excess weight. 1 …”
mentioning
confidence: 99%
“…In other words, it is possible to improve endothelial dysfunction using medical treatment and exercise, even without completely reversing it. 16 , 17 …”
mentioning
confidence: 99%
“…Perhaps the development of biomarkers may strengthen the clinical reasoning of cardiovascular diseases from the point of view of endothelial dysfunction. 17 - 19 …”
mentioning
confidence: 99%